A Simple Aluminum Bromide-Promoted Diastereoselective Synthesis of Panduratin A Derivatives - Thy, Chun Keng; Murthy, Sudtha; Lee, Yean Kee; Yaeghoobi, Marzieh; Abd Rahman, Noorsaadah; Chee, Chin Fei (Thieme Publishing, 2018)
A facile diastereoselective synthesis of panduratin A derivatives using commercially available aluminum(III) bromide is reported. The effect of substituents on the Diels-Alder reaction of various trans -chalcones with (E)-ocimene was investigated. A series of panduratin A derivatives were prepared in moderate to good yields.